2020
DOI: 10.1021/acsami.0c12988
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Free Tandem Reaction Strategy for Surface-Enhanced Raman Scattering Detection of Glucose by Using the Composite of Au Nanoparticles and Porphyrin-Based Metal–Organic Framework

Abstract: In this work, an S hybrid nanosheet with multiple functions is synthesized by in situ modification of gold nanoparticles (AuNPs) onto two-dimensional (2D) metalloporphyrinic metal–organic framework (MOF) (Cu-tetra­(4-carboxyphenyl)­porphyrin chloride­(Fe­(III)), designated as AuNPs/Cu-TCPP­(Fe). Cu-TCPP­(Fe) nanosheets contribute peroxidase-like activity, and AuNPs have glucose oxidase (GOx) mimicking performance, which induce the cascade catalysis reactions to convert glucose into hydrogen peroxide (H2O2), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(52 citation statements)
references
References 42 publications
0
52
0
Order By: Relevance
“…Alternatively, surface-enhanced Raman scattering (SERS) as an ultrasensitive spectroscopic analytical technique can identify and quantify analytes based on their unique molecular vibrational fingerprints. Moreover, SERS is resistant to photobleaching and self-quenching and has a lower background signal than fluorescence imaging. However, on the one hand, monitoring H 2 O 2 released from cells is challenging due to its rapid diffusion, self-transformation, and dilution to ultralow concentration in the cellular microenvironment. , On the other hand, it is difficult to detect molecules with low Raman scattering cross-sections or with poor affinity to the SERS-active substrates. , These problems severely limit the application of SERS in H 2 O 2 detection.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, surface-enhanced Raman scattering (SERS) as an ultrasensitive spectroscopic analytical technique can identify and quantify analytes based on their unique molecular vibrational fingerprints. Moreover, SERS is resistant to photobleaching and self-quenching and has a lower background signal than fluorescence imaging. However, on the one hand, monitoring H 2 O 2 released from cells is challenging due to its rapid diffusion, self-transformation, and dilution to ultralow concentration in the cellular microenvironment. , On the other hand, it is difficult to detect molecules with low Raman scattering cross-sections or with poor affinity to the SERS-active substrates. , These problems severely limit the application of SERS in H 2 O 2 detection.…”
Section: Introductionmentioning
confidence: 99%
“…As reported by previous studies, nanozymes with peroxidase-like activity have been confirmed to catalyze the Raman-inactive reporter (i.e., LMG) into Raman-active reporters (i.e., MG) in the presence of H 2 O 2 . 35,42 To study the Raman signal amplification catalyzed by the peroxidase-like CeO 2 nanozymes, LMG and H 2 O 2 were selected as the CeO 2 nanozyme substrates. A total of 50 μL of CeO 2 nanozyme (10 mg/mL) and 400 μL of LMG (100 mmol/L) were added to the Tris−HCl buffer (50 mmol/L, pH 7.0) and uniformly mixed.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Hu et al developed AuNPs and porphyrin-based MOFs composites (AuNPs/Cu-TCPP(Fe)) for the detection of glucose by exploiting a SERS-transduction method. [187] The AuNPs/ Cu-TCPP(Fe) hybrid was prepared by in situ modification of AuNPs onto the Cu-TCPP(Fe). The authors claimed that AuNPs mimicked the GO x like properties, while Cu-TCPP(Fe) acted as a peroxidase mimicking.…”
Section: (16 Of 28)mentioning
confidence: 99%